África, travessia e liberdade: Uma viagem historiográfica pela a poesia de Castro Alves (1863-1870) - Silva, Rodrigo Ferreira da (2017)
The objective of this work is to analyze how Castro Alves in his poetics understood the construction of Africa, as well as his representation of the transatlantic crossing, and also in this perspective, to understand the role of constructing an allusion to Palmares, clearly a resistance of the blacks to the slave system, which we call Africa to Brazilian. In this way, we intend to travel in the representation that the poet made about Africa in Vozes D'África (1868), the crossing in Navio Negreiro (1868) and the construction of a freedom, in slavery soil in Salute to Palmares (1870). Methodologically, for this research was selected only three poems to understand his thinking, present in his work The Slaves (1883), which brought together his poetic production posthumously, always positioned contrary to slavery and the situation of the Negro by Brazilian slave society. As a theoretical support, we base our studies on Edison Carneiro (1937), Costa e Silva (2006), Afrânio Peixoto (1947), João José Reis (1995), Rocha Pitta (1952), Nina Rodrigues (1976) and Paul Gilroy) that allied with other researchers we could understand this archeology of the thought of Castro Alves. In spite of the innumerable incongruities that the poet presents in his poetry, he dedicates himself to uncommon questions that is the black and his enslavement, presenting him sometimes as participant, agent and fighter, now presents as suffering and docile, leaving puzzles in his thoughts about freedom in his poetics.